Integrating Behavioral Health and Primary Care in an Inner-City High School: Expanded Care in a School-Based Clinic in Mississippi, 2018-2020. (May 2023) - Duck, Angela A.; Carr, Kayla; Lim, Crystal S.; Robinson, Jennifer C.
Adolescence, a critical and rapid stage of human development, requires innovative approaches in the provision of health care. With considerable mental health issues occurring among adolescents, an urgent need exists to address their mental and behavioral health. School-based health centers can provide an important safety net, particularly for young people who lack access to comprehensive and behavioral health care. We describe the design and implementation of behavioral health assessment, screening, and treatment services in a primary care school-based health center. We reviewed primary care and behavioral health measures as well as the challenges and lessons learned of this process. Five hundred and thirteen adolescents and young adults aged 14-19 years from an inner-city high school in South Mississippi were screened for behavioral health issues from January 2018 through March 2020, and all 133 adolescents deemed at risk for behavioral health issues received comprehensive health care. Lessons learned included the importance of recruiting behavioral health providers to ensure sufficient staff, establishing academic–practice arrangements to ensure funding, increasing student enrollment by improving the return rate of consent for care, and enhancing data collection through process automation. This case study may help inform the design and implementation of integrated primary and behavioral health care in school-based health centers.